PELAKSANAAN PENDIDIKAN KARAKTER DI MADRASAH TSANAWIYAH NEGERI “X” JAKARTA - Chusnah, Miftachul (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2013)
This article aims to describe and analyze the influence of guidance counseling and extracurricular to the character in class IX student of State Islamic Junior High School “X” Jakarta. The population sample was taken as 272 and as many as 135 research students. Instruments used in data collection is questionnaire. The results were analyzed with descriptive statistics with regression and correlation techniques. The study concluded that: (1) Guidance counseling and extra curricular positive effect on the character of the students, (2) the better implementation of the guidance counseling and extra-curricular activities that will better the likely increase learners’ character of MTs N “X”.